Analisis Pengalaman Pembelajaran Jarak Jauh terhadap Mahasiswa Difabel Tunanetra Universitas Brawijaya - Gery Raharrdian Sony Ricardo; Diah Priharsari; Buce Trias Hanggara (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
At the time the Covid-19 pandemic had made many changes and the impact of this pandemic was initially a face-to-face learning system in the classroom and then distance learning was implemented. The distance learning procedure used by Brawijaya University is with two teaching models between lecturers and students based on the time of the learning process, namely synchronous and asynchronous. The purpose of this study is to find out the experiences during the distance learning process by students with visual impairments and problems that can be solved or assisted by applications in the learning process. The data collection experience analysis using a semi-structured interview method. The respondents studied were 3 students with disabilities with visual impairments (blindness) adjusting the availability of respondents who were willing to conduct interviews related to research. Aspects of College Student Characteristic, Instructor Characteristic, Learning Environment, Information Technology, Knowledge Technology, and Support as well as problems encountered related to Technology and Assistance were analyzed. Then the data is processed using the Atlas.ti application by means of thematic coding analysis. The results of the analysis that are known are descriptive explanations of the conditions experienced by students then accessibility to documents has not been evenly distributed, the inability and limitations of applications in carrying out an order thus require a companion under certain conditions.